Communication Skills Development as a Gen-Z Core Competency at SMKN 1 Cihampelas West Bandung, West Java Province - Suarsa, Senny Handayani; Widyana, Suci Fika; Rezza, Ali Mohamad; Annisawati, Asaretkha Adjane (Universitas Mathla'ul Anwar Banten, 2024)
Generation Z (Gen-Z) are individuals born between the mid-1990s and 2000s. Middle school students are part of the Gen-Z group. As digital natives, Gen-Z often doesn’t need technological assistance, considering they are already used to and familiar with technology. However, their ability to adapt to technology sometimes differs from their ability to communicate directly in public. By mastering public speaking, Gen-Z can build self-confidence and make good presentations to convey their ideas so that effective communication can be achieved, especially for SMKN 1 Cihampelas students whose main target after graduating is to enter the world of work immediately. Lack of self-confidence makes students feel embarrassed and afraid to speak in public. Therefore, it is necessary to improve communication skills, which aim to provide knowledge about Public Speaking, which will later help grow students' self-confidence in speaking in public, make it easier for them to adapt to the work environment, help them get support, get a job, and career, through public speaking training. The training stages consist of preparation, implementation, evaluation, and reporting. As a result of this training, participants are now equipped with the knowledge and skills to effectively engage in public speaking and apply them in their future professional endeavors.